Distance effects on 802.11g/n performance of difference transmit power / Muhamad Ridzuan Abdullah Muzafar Shah - Abdullah Muzafar Shah, Muhamad Ridzuan (2014)
This paper describes the concepts and methodology of the 802.11g and 802.11n wireless networking standards by using different powers in different distances of transmission. This paper investigates the mobile client to server network performance by using Windows 7 as the operating system for mobile client while FreeBSD functions as the server. The evaluation has looked into the impact on TCP while operating in different transmission powers at different distances. The results show that the 213mW transmit power gave the highest throughput with the best time in transferring 100MB file for both 802.11n and 802.11g. However, the 802.11n protocol has higher throughput compared to the 802.11g in every scenarios.